Síntese de derivados benzofenônicos com potencial antifúngico e anti-leishmania - Maciel-Rezende, Claudia Mara (2012)
The benzophenones are used largely as synthetic intermediary in the chemical and pharmaceutical industry. They are objective of continuous investigations of biological interest due to properties, such as: insecticide, anti-aggregation platelet, inhibitory of xanthine oxidase, antioxidant, anti-microbial, anti-inflammatory and anti-proliferative. In this work it is described the synthesis of the methyl, butyl and prenyl derivatives of the benzofenones 2,4-di-hydroxybenzofenone, 4-hydroxybenzofenone and 4,4'-di-hydroxybenzofenone, following by the characterization for techniques spectroscopic and spectrometric (infrared, ultraviolet-visible and nuclear magnetic resonance and mass spectrometry). The compounds were submitted to the tests of antioxidant activity for the mechanism of scavenging of free radicals DPPH, inhibitory of xanthine oxidase and anti-microbial (bacteria, fungi and Leishmania) in order to link the chemical structure with the biological activity of the analyzed compositions. Flowed tested they didn't present significant results for the antioxidant activity in relation to the ascorbic acid pattern, once the substitutions increased the lipophilic character of the molecules in relation to the ascorbic acid pattern. In the test of inhibition of xanthine oxidase, flowed obtained they were not appraised due to yours no solubility in the middle. For the anti-bacterial (Gram-positive and Gram-negatives) activity, derived them didn't also present inhibitory activity in the tested microorganisms. In the activity anti-fungal, the butyl derivative was more active than the fluconazole. In the activity leishmanicida (promastigote form), the methyl and prenyl derivatives presented significant inhibitory activity when compared to amphotericin-B. The obtained results evidenced that the variation of the lipophilicity of the molecules is an important point for the biological activity and that some structural modifications accomplished in the benzofenonas took her flowed more potent, selective and little toxic against different types of microorganisms pathogenic.